Why MMORPG players do what they do: relating motivations to action categories. (12th November 2010) - Suznjevic, Mirko; Matijasevic, Maja
This paper presents an analysis of relations between player motivation and behaviour in a Massively Multiplayer Online Role-Playing Game (MMORPG). Player motivation is measured in terms of percentile ranks of motivational components for MMORPG players defined by Nick Yee. Player behaviour is described through previously defined action categories for MMORPGs (Trading, Questing, Dungeons, Raiding, Player versus Player Combat, and Communication). We conduct a player survey and perform measurements on the client side for a group of 104 players of World of Warcraft. Additionally we examine the importance of both voice and textual communication in MMORPGs.